Mobile electrical capacitance tomography (ECT) development for liquid-gas flow measurement - Chan, Kok Seong; Pusppanathan, Jaysuman; Abdul Rahim, Ruzairi; Susiapan, Yvette Shaan-Li; Phang, Fatin Aliah; Rahiman, Mohd Hafiz Fazalul; Awang, Zubaidah; Ahmad, Anita; Abdul Wahid, Herman; Mohamad, Elmy Johana; Ridzuan Aw, Suzanna (Penerbit UTM Press, 2015)
Electrical capacitance tomography (ECT) system is useful to obtain information on spatial distribution of dielectric material mixture inside a vessel. This paper discusses a sixteen-electrode mobile ECT sensing system which is developed non-invasively and non-intrusively. Emphases on the software development aspects are presented in several sections; initialization part, normalization part, calibration part, hardware communication part and the image reconstruction part. Thus, the liquid-gas concentration profile of the ECT system is successfully acquired using the software developed.